Intuitive Ethics and Political Orientations: Testing Moral Foundations as a Theory of Political Ideology. Issue 2 (8th April 2016) - Smith, Kevin B.; Alford, John R.; Hibbing, John R.; Martin, Nicholas G.; Hatemi, Peter K.
Abstract: Originally developed to explain cultural variation in moral judgments, moral foundations theory (MFT) has become widely adopted as a theory of political ideology. MFT posits that political attitudes are rooted in instinctual evaluations generated by innate psychological modules evolved to solve social dilemmas. If this is correct, moral foundations must be relatively stable dispositional traits, changes in moral foundations should systematically predict consequent changes in political orientations, and, at least in part, moral foundations must be heritable. We test these hypotheses and find substantial variability in individual‐level moral foundations across time, and little evidence that these changes account for changes in political attitudes. We also find little evidence that moral foundations are heritable. These findings raise questions about the future of MFT as a theory of ideology.